Psychological Features of the Pedagogical Process in a Medical University - Shoyimova Shokhista Sanakulovna (International Journal on Integrated Education, 2023)
The article presents a study of the quality of education within the framework of the quality management system in a medical university. The main attention is paid to the psychological and pedagogical conditions of the quality of education, the results of a survey of satisfaction with the quality of education by the educational process within the discipline "Psychology and Pedagogy" are shown.